KARAKTERISTIK ENDAPAN NIKEL LATERIT BLOK O DAERAH BUNTA, KABUPATEN BANGGAI - Ghaneswara, Oka Arin; Permana, Aang Panji; Hutagalung, Ronal (J SIG (Jurnal Sains Informasi Geografi), 2023)
The research area is in Block O Bunta Region, Banggai Regency. The research area includes areas with laterite nickel deposits in Central Sulawesi Province. Based on the Luwuk Sheet Geological Map, the Bunta area is included in the Ku Formation (Ultramafic Complex) composed of serpentinite, gabbro, basalt, and schist rocks. The aim of this study was to analyze the characteristics of laterite nickel deposits in Block O, Bunta Region, Banggai Regency. To achieve this goal, several research methods were carried out, namely field geological survey methods and laboratory analysis. The field geological survey includes detailed geological mapping and coring drilling data collection. The field geological survey includes observations of rocks and geomorphology of the study area. Meanwhile, laboratory analysis includes coring data analysis. The total drilling samples analyzed came from 40 drill points. The results and discussion show that the geomorphology of the study area is classified into denudational hill units. The lithology in the study area based on the analysis results is serpentinized peridotite. The characteristics of nickel laterite deposits in the study area consist of limonite and saprolite zones. The limote zone has a characteristic reddish brown color dominated by hematite minerals and yellowish brown dominated by goethith minerals. While the saprolite zone is dominated by a greenish-yellow color with its constituent minerals namely serpentine, goethith, silica.